Electrical performance of 0.5 µm MOSFET on bond-and-etch-back silicon-on-insulator(BESOI) substrate - Abdullah, Wan Fazlida Hanim; Mohd Sidek, Roslina; Mohd Saari, Shahrul Aman; Ahmad, Mohd Rais (2002)
0.5 µm gate length MOSFET is fabricated on Bond-and-Etch-Back Silicon-On-Insulator (BESOI) substrate using bulk CMOS technology. For the purpose of silicon layer thickness adjustment, sacrificial oxidation is implemented on the device layer of 1.5 ± 0.5 µm device layer and 2 µm buried oxide thickness. Effects of the BESOI substrate and prior sacrificial oxidation on the threshold voltage, drive current and off-state leakage current are investigated from preliminary electrical measurements. Comparison between devices fabricated on bulk silicon and BESOI substrate were carried out. Results are presented in intrinsic transistor performance plots illustrating the relation and variation of critical parameters over the entire wafer.